2020
DOI: 10.1007/s11030-020-10151-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking studies, molecular dynamics and ADME/tox reveal therapeutic potentials of STOCK1N-69160 against papain-like protease of SARS-CoV-2

Abstract: SARS-CoV-2 is a new strain of Coronavirus that caused the pneumonia outbreak in Wuhan, China and has spread to over 200 countries of the world. It has received worldwide attention due to its virulence and high rate of infection. So far, several drugs have experimented against SARS-CoV-2, but the failure of these drugs to specifically interact with the viral protease necessitates urgent measure to boost up researches for the development of effective therapeutics against SARS-CoV-2. Papain-like protease (PLpro) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…The docking protocol was validated by computing the relative binding free energies of the docked protein-ligand complex [ 74 ]. Prime MM-GBSA calculates various energy components of the protein, ligand and protein-ligand complex.…”
Section: Resultsmentioning
confidence: 99%
“…The docking protocol was validated by computing the relative binding free energies of the docked protein-ligand complex [ 74 ]. Prime MM-GBSA calculates various energy components of the protein, ligand and protein-ligand complex.…”
Section: Resultsmentioning
confidence: 99%
“… 31 It predicts the binding model and energy of compounds with the active pose of target proteins. 32 The compounds in this study demonstrated varying degree of binding affinities for the targets as shown in Table 4 . The binding affinity of drimenin (−9.1 kcal/mol) for α-synuclein was observed to be higher than the standard ligand (donepezil: −8.7 kcal/mol).…”
Section: Discussionmentioning
confidence: 95%
“…The reliability of the molecular docking result was determined by estimating the binding free energy through the Prime MM-GBSA module of Maestro. This approach is one of the most reliable methods of validating docking results as it helps to determine the stability of the receptor-ligand complex 41,42 . This denotes that a favorable binding free energy correlate to a reliable output from molecular docking study.…”
Section: Discussionmentioning
confidence: 99%